Opinion: The Pharmacometrics of Infectious Disease. (28th August 2013) - Davies, GR; Hope, W; Khoo, S
Abstract : The application of pharmacometric principles to the treatment of infectious diseases must address important biological issues across the diversity of pathogenic organisms. Recent applications of pharmacometric tools in this therapeutic area have had important translational impact not only in drug development but on real‐world clinical practice. The fruitful fusion of preclinical and population methodologies promises increasingly personalized and mechanistic approaches. CPT: Pharmacometrics & Systems Pharmacology (2013) 2, e70; doi:10.1038/psp.2013.46 ; published online 28 August 2013